Design and Optimization of a Phase-Tunable Mixer Based on Cascaded Dual-Drive Mach–Zehnder Modulator Considering Nonlinear Behavior of Modulator - Ebrahim Darabi; Heidar Keshavarz (International Journal of Optics)
This paper proposes a novel phase-tunable mixer based on a cascaded dual-drive Mach–Zehnder modulator (DDMZM), designed to address the critical need for simultaneous frequency mixing and precise phase control in phased array antennas. Unlike conventional mixers, the proposed structure uniquely combines frequency mixing and phase tuning, enabling optimal 360-degree phase shifting with constant power. To achieve this, we developed an innovative analytical model that incorporates the nonlinear behavior of electro-optic modulators in the DDMZMs. This model enables accurate prediction of power and phase for each mixed frequency in the output spectrum. By systematically adjusting four degrees of freedom—the bias voltages of the electro-optic modulators—we present a comprehensive dataset visually represented as a graph to demonstrate the power-phase relationship. A novel approach maps the optimization problem of achieving desired phase shifts onto solving the shortest path problem, providing a fresh perspective on mixer design. This methodology ensures precise phase control and efficient system performance. The novelty and practicality of our structure are validated through both analytical predictions and verification using commercial simulation software, underscoring its potential for high-performance phased array applications.